Bioceramic/Poly (glycolic)-poly (lactic acid) composite induces mineralized barrier after direct capping of rat tooth pulp tissue - Alfonso Gala-Garcia; Karina Imaculada Rosa Teixeira; Francisco Henrique Lana Wykrota; Rubén Dario Sinisterra; Maria Esperanza Cortés (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this study was to observe the histopathological pulp response following direct pulp capping of mechanically exposed teeth in rats with a composite of beta-tricalcium phosphate-hydroxyapatite bioceramic (BC) and poly (glycolic)-poly (lactic acid) (PLGA) material or a calcium hydroxide [Ca(OH)2] material, compared to BC alone and a negative control of water. Pulp of the maxillary molars was exposed, followed by capping with the experimental material. The pulpal tissue response was assessed post-operatively at 1, 7, 14 and 30 d, followed by histological analysis. The Ca(OH)2 group exhibited severe acute inflammatory cell infiltration at day 14. However after 30 d, a new hard tissue with macro porous obliteration of the pulp chamber and a characteristic necrotic area had appeared. BC and Ca(OH)2 capping were associated with moderate inflammation and dentinal bridge similar. Meanwhile, in the BC/PLGA composite group, there was moderate inflammatory infiltrate and formation of a dense and complete dentinal bridge. In conclusion, the BC/PLGA composite material showed a large zone of tertiary dentin, and effectively reorganized the dentin-pulp complex.